Registration system and UTM games decision using the website application - Ahmad Fauzy, Fatin Azura; Ali Shah, Zuraini; Saedudin, Rd Rohmat; Kasim, Shahreen; Azadin, Ayu Alyani; Ahmar, Ansari Saleh; Hidayat, Rahmat (Science Publishing Corporation Inc., 2018)
UTM Games is an annual sports tournament organized by UTM Sports Excellence involving students, staff team, PELUAS (International Student Team) and International Campus Kuala Lumpur. There are 14 types of contested games such as volleyball, soccer, squash, netball, bowling, badminton, kayaking, futsal, sepak takraw, table tennis, tennis, basketball, cycling, and lawn bowls. Currently registration and review of result for UTM Games are still done manually and on papers for some of the residential colleges. While for some other residential colleges, registration and review of results are done by web applications such as in Tun Ghafar Baba College (KTGB). Therefore, the Registration and Review of Results for UTM Games using Smart Phone is developed because most users nowadays have a smartphone and internet access. In addition, the system allows the user to see the results of UTM Games without having to log into social sites such as Facebook. The system is developed using ASP.Net technology and Microsoft Visual Studio 2010. The methodology used in developing this system is a prototype evolving methodology. This methodology allows the user to provide feedback and insights to add dynamically. The prototype will be modified according to the views and feedback given. The system is a platform to make it easier for managers to register for the game. In addition, the system is developed to enable students to review results from UTM Games more quickly and accurately